Pengaruh Efektivitas Sistem Informasi Akuntansi, Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada BPR Kota Denpasar - Ayu Listya Anggita Wenantari; I Gusti Ayu Ratih Permata Dewi (Universitas Warmadewa, 2026)
An accounting information system is an information system specifically designed to facilitate all matters related to accounting. The purpose of this study is to provide an empirical overview of the effectiveness of the accounting information system, work motivation, work discipline, and the influence of the work environment on employee performance. The survey was conducted across all Rural Banks (BPR) in Denpasar City. The survey utilized a sample of 99 respondents. Data were collected using public information. The data analysis method used in this study is multiple linear regression analysis. Several studies indicate that the accounting information system, motivation, discipline, and environmental effectiveness influence employee performance. It is expected that the management of Rural Banks (BPR) in Denpasar City continuously improve the effectiveness of their accounting information systems, as the success of a company's information system depends on how the system is executed.